1985
DOI: 10.1073/pnas.82.9.2955
|View full text |Cite
|
Sign up to set email alerts
|

Specificity analysis of mouse monoclonal antibodies defining cell surface antigens of human renal cancer.

Abstract: Six mouse monoclonal antibodies (mAbs) defining separate systems of cell surface antigens of cultured human renal cancer were tested for reactivity with normal fetal and adult tissues and with neoplastic tissues. Five of the mAbs identified glycoproteins of Mr 160,000 (designated S4), Mr Mr 140,000 (F23), Mr 120,000 (S23 and S27), and Mr 115,000 (S22). The glycoprotein component of Mr 120,000 has been shown recently to be the adenosine deaminase binding protein (ADA-BP) and mAbS23 and mAbS27 define two distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0
1

Year Published

1987
1987
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(37 citation statements)
references
References 17 publications
1
35
0
1
Order By: Relevance
“…In contrast, we have detected gpl60 expression in most cultured and noncultured RCCs (2,5,6), suggesting that APA is a kidney differentiation antigen and not related to transformation. Similarly, murine APA (BP-1/C63) in pre-B lymphocytes is believed to define a differentiation stage unrelated to malignant potential (47).…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…In contrast, we have detected gpl60 expression in most cultured and noncultured RCCs (2,5,6), suggesting that APA is a kidney differentiation antigen and not related to transformation. Similarly, murine APA (BP-1/C63) in pre-B lymphocytes is believed to define a differentiation stage unrelated to malignant potential (47).…”
Section: Discussionmentioning
confidence: 45%
“…gpl60 was isolated from normal human kidney, which expresses high levels of this protein (1,2), by first enriching for glycoproteins with lectin chromatography followed by immunoaffinity purification using anti-gpl60 mAb S4. A comparison of the amino acid sequences of three gpl60 tryptic peptides to those in the translated GenBank data base (23) revealed incomplete homology to the BP-1/6C3 differentiation antigen (24), a murine early B-lymphocyte cell surface glycoprotein.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although to date, a small number of possible marker genes are known to predict RCC behavior more accurately, a reliable marker for early diagnosis of RCC has not been reported (15). Since RCC is believed to arise from proximal tubule epithelium (16,17) and in order to identify new prognosis markers for clear cell RCC, we have examined in the present study the relationship between CK18 and Snail expression in RCC. Our findings point to the existence of a relationship between CK18 and RCC progression as well as a role for Snail during this process.…”
Section: Introductionmentioning
confidence: 99%
“…17 However, there have been few reports on APA expression and its functional significance in tumor cells. [18][19][20] We have recently demonstrated that APA was expressed in neoplastic lesions of the uterine cervix, and its expression was upregulated as the lesion progresses from cervical intraepithelial neoplasms (CIN) toward invasive squamous cell carcinomas (SCC). 21 However, the regulatory mechanisms for APA expression and its functional role in the progression of cervical carcinoma remain to be clarified.…”
mentioning
confidence: 99%